"The Intel Microprocessors 8086 / 8088, 80186, 80286, 80386 and 80486 Architecture, Programming and Interfacing" - Brey (Barry B) (1995)
Intel Microprocessors ; 8086 / 8088 ; 80186 ; 80286 ; 80386 ; 80486 ; Architecture ; Interfacing
Keywords: Intel Microprocessors ; 8086 / 8088 ; 80186 ; 80286 ; 80386 ; 80486 ; Architecture ; Interfacing